How effective are financial incentives for teachers? - Scott A. Imberman (IZA World of Labor, 2015)
Concerns about poor student performance have led schools to diverge from traditional teacher compensation and base a portion of pay on student outcomes. In the US, the number of school districts adopting such performance-based financial incentives has increased by more than 40% since 2004. Evidence on individual incentives in developed countries is mixed, with some positive and some negligible impacts. There is less evidence for developing countries, but several studies indicate that incentives can be highly effective and far cheaper to implement. Innovative incentive mechanisms such as incentives based on relative student performance show promise.
Keywords: I21; I28; J33; J45; 330; teacher incentives; student achievement; pay-for-performance; merit pay